3D printed sandwich beams with bioinspired cores: Mechanical performance and modelling. (April 2021) - Peng, Chenxi; Fox, Kate; Qian, Ma; Nguyen-Xuan, H.; Tran, Phuong
Abstract: Triply periodic minimal surface (TPMS) based cellular structures have drawn increasingly attention due to their mathematically controlled topologies and promising mechanical properties. Here, we combine 3D-printing technique, experiments, theoretical formulation and numerical simulation to investigate a novel class of lightweight sandwich structures with TPMS cores. Sandwich structures with Primitive, Neovius and IWP core topologies are designed and fabricated using a 3D-printing technique. The bending properties, failure mechanism as well as energy absorption capacity of these TPMS sandwich structures are evaluated via a three-point bending test. A numerical model is developed to analyse the behaviours of the sandwich structures under bending loading. Theoretical formulation is employed to compare with the experimental data and numerical simulation. A good agreement is achieved between the attendant experimental data, theoretical formulation, and numerical simulation. In addition, a comprehensive parametric study is conducted to understand the effect of core topologies, relative density of the TPMS core, and geometrical parameters on the bending properties and energy absorption capacity of the sandwich structures based on the numerical model proposed. Both the relative density of the core and the geometrical designs of the TPMS sandwich structures exhibit a significant effect on the bending properties and energy absorption capacity. In contrast, the topologies of the TPMS cores have a limited effect on the bending properties at low relative density for designs with a thick face-panel. The sandwich structures with a Neovius core have better performance compared to other core topologies for designs with a thin face-panel. Overall, this study indicates that sandwich structures with TPMS cores could be designed to deliver desirable bending properties and energy absorption capacity, and the findings of this study provide insights into future designs of novel sandwich structures for various engineering applications. Highlights: A novel class of triply periodic minimal surface (TPMS) sandwich structures are designed. Samples are fabricated via 3D-printing and evaluated under three-point bending tests. A numerical model is developed and validated by experimental data and analytical results. A comprehensive parametric study is performed to reveal the effect of core topology and relative density.